Interpretation and Institutional Choice at the WTO - Gregory Shaffer; Joel Trachtman (Oñati Socio-Legal Series)
This article develops the framework of comparative institutional analysis for assessing the implications of judicial interpretation in the World Trade Organization (WTO). The analytical framework offers an improved means to describe and assess the consequences of choices made in treaty drafting and interpretation in terms of social welfare and participation in social decision-making. The analysis builds on specific examples from WTO case law. Our framework approaches treaty drafting and judicial interpretive choices through a comparative institutional lens — that is, in comparison with the implications of alternative drafting and interpretive choices for social welfare and participation in social decision-making processes. By deciding among alternative interpretations, the judicial bodies of the WTO effectively determine which social decision-making process decides a particular policy issue. That decision, in turn, can have profound domestic and international implications. While this article focuses on the WTO, the framework developed here has general relevance for understanding the interpretation of international and domestic legal texts from “law and economics” and “law and society” perspectives.